Impact of nanogap thickness on dielectric-modulated field-effect transistor biosensor performance for uncharged biomolecules detection - Jasmi, M.S.; Fathil, M.F.M.; Arshad, M. K. Md; Nuzaihan., M. N M.; Halim, N.H.A.; Rahman, S.F.A.; Ayoib, A.; Shaifullah., A. S M.; Mat Ibrahim, Masrullizam (2023)
Uncharged biomolecules sensing performance of dielectric-modulated field-effect transistor (DMFET) biosensor at various nanogap thickness via semiconductor device simulation tool was assessed in this work. The device structures with 10 nm-, 15 nm-, and 20 nm-thick nanogap were constructed for this investigation. Each device structure was applied with dielectric constant ranging from 2 to 7 at the nanogap representing the presence of various biomolecules. These device structures were electrically simulated by supplying gate voltage from 0 V to 2 V and biased with drain voltage of 0.05 V for linear region of operation. Based on the extracted drain current, the reduction of nanogap thickness increase capacitance at the nanogap region. In additional, increase in nanogap's dielectric constant causing an increase of its capacitance, and translated into higher output drain current. Sensitivity calculation and analysis shows DMFET biosensor with 10 nm-thick nanogap demonstrated the highest sensitivity with 6.896 μA/dec, which possibly permit enhanced sensing of uncharged biomolecule.